Pengaruh Media Video Animasi terhadap Kemampuan Mengenal Huruf Vokal pada Siswa Disabilitas Intelektual Ringan Kelas IV - Ledu, Elisabeth Lusitania; Prystiananta, Nostalgianti Citra; Nurhadiyati, Arifah (JOEAI (Journal of Education and Instruction), 2025)
This study aims to determine the effect of animated video media on the ability to recognize vowels (a, i, u, e, o) in fourth-grade students with mild intellectual disabilities at Jember State Special Needs School. The research method employed is Single Subject Research (SSR) with an A-B design, consisting of two phases: the baseline phase (A), comprising five sessions, and the intervention phase (B), comprising eight sessions. The results of the analysis in the conditions show that the baseline phase has a percentage score of 35%–50% with a mean level of 42% and a stability range of ±3.7. The data within the stability range is only 1 out of 5 sessions, or 20%, so the data in the baseline phase is declared unstable. In the intervention phase, the percentage score increased from 45% to 85%, with a mean level of 68.7% and a stability range of ±6.3. The data in the stability range is only 2 out of 8 sessions, or 25%, so the intervention phase is also declared unstable. Although both phases exhibited unstable conditions based on the criteria (<80%), there was a significant increase in ability levels from Phase A to Phase B, from a high score of 50% to 85%, as well as a positive level change of +20. No overlap in data (0%) was found, which strengthens the intervention's influence on changing the target behavior. In conclusion, animated video media has been shown to have a positive effect on improving vowel recognition skills in students with mild intellectual disabilities. This study recommends the use of visual-interactive media such as animated videos in special education learning at special needs schools (SLB).   Keywords: Animated Video, Vowels, Intellectual Disability